2008
DOI: 10.1007/s10533-008-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen release from surface sand of a high energy beach along the southeastern coast of North Carolina, USA

Abstract: This study examined changes in dissolved organic nitrogen (DON) and dissolved inorganic nitrogen (DIN) in coastal seawater after exposure to sand along a high energy beach face over an annual cycle between April 2004 and July 2005. Dissolved organic nitrogen, NO 3 -, and NH 4 + were released from sand to seawater in laboratory incubation experiments clearly demonstrating that they are a potential source of N to underlying groundwater or coastal seawater. DON increases in seawater, after exposure to surface san… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The significant, positive effects of 1-day rainfall on PP and PB suggest that rainwater may pump pore water through the highly permeable beach and thereby enhance nutrient fluxes into the nearshore zone. Our observations of pore water nutrients (Table 2b) and other studies of beach nutrient dynamics (Campbell andBate, 1996, 1997;Avery et al, 2008) support this inference. Questions remain about the magnitude of this effect vs. other nutrient supply mechanisms, such as estuarine outwelling and in situ regeneration, but the rainfall effects suggest the overall importance of nutrient supply in regulating surf zone production.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…The significant, positive effects of 1-day rainfall on PP and PB suggest that rainwater may pump pore water through the highly permeable beach and thereby enhance nutrient fluxes into the nearshore zone. Our observations of pore water nutrients (Table 2b) and other studies of beach nutrient dynamics (Campbell andBate, 1996, 1997;Avery et al, 2008) support this inference. Questions remain about the magnitude of this effect vs. other nutrient supply mechanisms, such as estuarine outwelling and in situ regeneration, but the rainfall effects suggest the overall importance of nutrient supply in regulating surf zone production.…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…One caution must be considered, however, in that low biomass in such high-energy, high-light environments does not necessarily equate to low production. Ocean beaches may experience relatively high nutrient flux rates (Avery et al, 2008) that, coupled with high light levels, might drive high production that is masked by high grazing and/or high physical removal rates, so we do not interpret low biomass as evidence that benthic microalgae on beaches are unproductive. Lack of such productivity data in the literature likely arises from the extreme challenges of measuring benthic microalgal production in such a physically dynamic environment.…”
Section: Discussionmentioning
confidence: 98%
“…It would have been overestimated by 8000 tons per year if active CO2 degassing between the forest soil aquifer and the supratidal beach had been neglected. High-energy sandy beaches are recognized as environments in which organic matter mineralization and recycling of the associated nutrients are very active (Avery et al, 2008;Rauch et al, 2008;Rocha, 2008;Anschutz et al, 2009;Dugan et al, 2011;Charbonnier et al, 2013). Previous studies at the Truc Vert Beach revealed that oxygen consumption through aerobic respiration takes place in the intertidal recirculation cell (Anschutz et al, 2009;Charbonnier et al, 2013).…”
Section: Fluxes Of Carbon From the Freshwater End-membermentioning
confidence: 99%